2021
DOI: 10.2147/jir.s330356
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Progranulin and Soluble Vascular Cell Adhesion Molecule-1 in Patients with COVID-19

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with the angiocentric inflammation and angiogenesis, yet the molecules involved in this process remain to be determined. Methods We did a cross-sectional study of a cohort of patients with COVID-19 in Zunyi, China between February 1 and March 30, 2020. Serum concentrations of PGRN were determined by enzyme-linked immunosorbent assay in patients with COVID-19 at hospital admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…showed elevated VCAM-1 concentrations, while ICAM-1 and E-selectin did not differ in cases vs. disease controls. In line with these findings, Cugno and Yao ( 19 , 37 ) showed no difference in E-selectin concentrations between mild to moderate COVID-19 cases and healthy controls. Our results regarding the cellular adhesion molecules are in line with these studies, but we demonstrate markedly lower E-selectin concentrations in cases vs. controls, mostly driven by control patients with bacterial pneumonia.…”
Section: Discussionmentioning
confidence: 54%
“…showed elevated VCAM-1 concentrations, while ICAM-1 and E-selectin did not differ in cases vs. disease controls. In line with these findings, Cugno and Yao ( 19 , 37 ) showed no difference in E-selectin concentrations between mild to moderate COVID-19 cases and healthy controls. Our results regarding the cellular adhesion molecules are in line with these studies, but we demonstrate markedly lower E-selectin concentrations in cases vs. controls, mostly driven by control patients with bacterial pneumonia.…”
Section: Discussionmentioning
confidence: 54%
“…Serum protein expression in the COVID-19 patients was examined in the literature, and there was no difference in IL-6 levels in the SARS-CoV-2 positive patients compared to the patients with similar symptoms and disease severity but negative for SARS-CoV-2, whereas a specific increase of the PGRN level has been shown [ 26 ]. Yao et al [ 27 ] found that serum VCAM-1 and PGRN levels were higher in the patients with COVID-19 than in the healthy controls in their study of PRGN and VCAM-1 levels in the patients with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al . [ 34 ] reported that patients with COVID-19 had higher PGRN levels than healthy controls, and that these levels decreased after successful treatment. In the present study, we demonstrated that PGRN levels were higher among ICU-treated patients; however, these values were not predictive of mortality in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%